PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 7 PADANG - Mardianto, Yoki (Departemen Matematika, 2024)
Understanding mathematics concept is very important for students to master, because mathematics concepts are interrelated so that learning them must be coherent and continuous. But the facts in the field, this level of understanding for class VIII students at SMP Negeri 7 Padang is still in the low category. The author provides a solution, namely the use of the think pair square learn model. This studying aims to see the difference in conceptual understanding of students who use think pair square whether it is superior to convention learning. The type of research used is quasi experiment with static group design. The population is students of class VIII SMP Negeri 7 Padang, class VIII.3 and VIII.2 as the sample class. The finaly test in the form of an essai as an instrument. After the t-test was conducted, the P-value=0.015 was achieved. Because the P-value <0.05 consequently reject . Therefore, it is conclud that the level of students understanding the concept using think pair square is higher than using conventional.Keywords— Think Pair Square, Understanding of Mathematics Concept, Conventional Learning.